Exogenous Estradiol Benzoate Induces Spermatogenesis Disorder through Influencing Apoptosis and Oestrogen Receptor Signalling Pathway. Issue 1 (18th December 2015) - Lei, X; Cui, K; Liu, Q; Zhang, H; Li, Z; Huang, B; Shi, D
Contents: As the exact role for exogenous oestrogen in spermatogenesis is not fully understood, the aim of this study was to investigate the effect of estradiol benzoate (EB) exposure to male mice on their spermatogenesis and fertility. Sixty male mice aged 4 weeks were randomly divided into three groups, including a control group and two treatment groups. The mice of the control group were injected with 250 μl paraffin oil only by every other day subcutaneous injection for 4 weeks. Meantime, the mice of the treatment groups were injected with EB at the concentration of 5 or 10 mg/kg, respectively. Results showed that EB slowed down the body weight gains and generated testicular atrophy with spermatogenesis disorder compared with that of the control mice, and consequently induced their infertility. Moreover, the number of TUNEL‐positive cells in the testis of EB‐treated mice was significantly increased with the EB concentration rise. In comparison with controls, the mRNA expression level of pro‐apoptosis factors ( Fas, TNF, Cytochrome C, Apaf1, Chop, Caspase‐3, Caspase‐8, Caspase‐9 and Caspase‐12 ) and key genes in oestrogen receptor (ER) signalling pathway ( ER α, ER β, Erk1/2, Hsp90 and DAX‐1 ) were upregulated in the testes of the treatment groups. Furthermore, Western blotting results proved the protein expression level of Fas,  TNF, Cytochrome C, Chop, Caspase‐3, cleaved Caspase‐3, Caspase‐9, Erk1/2 and Hsp90 were upregulated, and the phosphorylation level of Erk1/2 was also increased. These results indicate that EB may impair spermatogenesis through influencing the apoptosis and ER signalling pathway.